Accelerated teaching and the achievement of the high school students in mathematics - Tingson, Ellin A. (2008)
This quasi-experimental research study aimed to know which of the two approaches - the accelerated teaching method or the conventional way of teaching, would have a better effect on the achievement of the students in high school mathematics. Eighty-two second-year students from two classes were involved. The research instruments, which were tested and validated by two experts of Mathematics and curriculum, consists of lesson plans with the same instructional content but with different approaches. Based on the findings, there was a significant difference between the effects of accelerated teaching method over the conventional teaching method. The accelerated teaching method seemed to improve the achievement of students in mathematics. In addition, it was observed that students exposes to the accelerated teaching method seemed to react positively to it.